A New Approach to Financial Regulation at the European Level - Ioana Laura Valeanu (CES Working Papers, 2015)
With the recent financial and economic crisis onset, a fragility of the financial system became apparent, under the form of a series of vulnerabilities and failures with a strong destabilizing impact on the economy. In this context, a new approach to financial stability has outlined itself, pleading for a more extensive financial regulation and macro-prudential supervision, complementary to the micro-prudential one. The objectives of this article are to highlight the context and need for a new financial regulatory framework and underline the main problems of the banking system the new European regulations addresses.
Keywords: G00; K20; 330; financial regulation; financial stability; banking system